Buttermilk as a wall material for microencapsulation of omega-3 oils by spray drying. (June 2020) - Zhang, Yuyu; Pang, Xiaoyang; Zhang, Shuwen; Liu, Liu; Ma, Changlu; Lu, Jing; Lyu, Jiaping
Abstract: Algal oil is rich in docosahexaenoic acid, which is an omega-3 polyunsaturated fatty acid. However, unsaturated bonds make docosahexaenoic acid vulnerable to oxidation. This work aimed to microencapsulate algal oil using buttermilk, alone or in combination with maltodextrin, as a wall material to protect it from oxidation and improve its stability by applying the spray drying method. Our study found that an increase in microcapsule oil content increased in microcapsule particle size, dispersion time and peroxide value and a decrease in microcapsule moisture content, bulk density and encapsulation efficiency. Moreover, the addition of different proportions of maltodextrin into the microcapsules increased the moisture content and particle size and decreased the encapsulation efficiency and oxidation stability. 33.3% oil and 66.7% buttermilk powder microcapsule obtained the highest encapsulation efficiency, The surface showed a regular and smooth spherical shape. 33.3% oil and 33.3% buttermilk powder mixed with 33.3% maltodextrin microcapsule achieved good encapsulation efficiency and the best stability during storage. Structures such as the milk fat globule membrane were also observed in both types of microcapsules. Highlights: Buttermilk has excellent properties as wall materials in encapsulating algal oil. Buttermilk-microcapsules significantly reduced the oxidation of algal oil. Structures like milk fat globule membrane were observed in buttermilk-microcapsules.